Analyzing the Impact of Service Quality on Satisfaction in E-Banking Services- An Empirical Study - Vijayanand S; Logesh Kumar S (KINERJA, 2021)
Customer satisfaction is now taking as a core issue in all the service oriented sectors and especially, banking institutions have considered this as a base point due to heavy competition and proffering higher services through digital and electronic mode. Even though they have offered better service, satisfaction level towards these E-banking services among the customers is not dynamic because of  not having adequate knowledge among them  in using these services which clearly reflected the under usage of customer knowledge management by the banking authorities. Taking into consideration, this study focusing the effect of E-Banking Services on customer satisfaction particularly in Public sector Banks of India through 667 customers selected through simple random sampling technique by getting the opinion through self administered questionnaire. Tools like Confirmatory Factor Analysis (CFA), Percentage Analysis, Karl Pearson’s Correlation, Multiple Regression Analysis, Comparing mean test were carried out and the result revealed that there existed a positive association between the factors under E-Banking Services and demographic variables too with the Customer Satisfaction and all factors were highlighted as a forecaster for Satisfaction.